Climate change vulnerability, adaptation measures, and risk perceptions at households level in Acholi sub-region, Northern Uganda. (April 2022) - Twecan, Dalson; Wang, Weiguang; Xu, Junzeng; Mohmmed, Alnail
Abstract: Uganda is among the world's susceptible countries to climate extremes, such as droughts (IPCC, 2007). This study assesses the risks associated with climate change vulnerability, adaptation techniques used by young smallholder farmers to ease its adverse effects on agriculture. A dataset of 600 randomly selected respondents was collected using the household survey method from Gulu, Kitgum, Pader, Amuru, Nwoya, and Lamwo districts. Finding reveals droughts, increased temperature, pests and diseases, degradation, and poor socioeconomic conditions as the main determinants of climate change. The main adaptation measures revealed were changing crop types, planting early-maturing crops, crop rotation, mixed cropping, and livelihood diversification. Lack of knowledge and information, poverty, inadequate governmental support, limited agricultural extension, insufficient financial capital, illiteracy, and markets were the main constraints hindering access and adoption of advanced adaptation measures. This research provides useful insights and evidence for policy implementation on household farm-level climate change vulnerability, adaptation measures, and risk perceptions in absorbing, adapting, and transforming from climate shocks and threats. The analysis implies that the government should provide agricultural extension services on climate vulnerability and adaptation measures, access to market, financial credits, knowledge and information, accessible livelihoods assets, and end-to-land grabbing. Overall, our results recommend that government authorities and relevant stakeholders integrate and implement climate change adaptation policies at local government operations to ease the vulnerability of smallholder farmers and augment their climate change absorptive, adaptive, and transformative abilities. Highlights: Determinants of farmers' adaptation to climate change in agricultural production in the central region of Vietnam. Weaponizing vulnerability to climate change. Smallholder farms' adaptation to the impacts of climate change Evidence from China's Loess Plateau. Climate change perception an analysis of climate change and risk perceptions among farmer types - Indian Western Himalayas. Farm households' perception on climate change and adaptation practices; a case from mountain district of Nepal.